Night-Break Experiments Shed Light on the Photoperiod1-Mediated Flowering . Issue 2 (13th April 2017) - Pearce, Stephen; Shaw, Lindsay M.; Lin, Huiqiong; Cotter, Jennifer D.; Li, Chengxia; Dubcovsky, Jorge
Abstract : Interruptions of long nights by short pulses of light ("night-break") for several days accelerates wheat flowering, but only in the presence of the PHOTOPERIOD1 gene. Abstract: Plants utilize variation in day length (photoperiod) to anticipate seasonal changes. They respond by modulating their growth and development to maximize seed production, which in cereal crops is directly related to yield. In wheat ( Triticum aestivum ), the acceleration of flowering under long days (LD) is dependent on the light induction of PHOTOPERIOD1 ( PPD1 ) by phytochromes. Under LD, PPD1 activates FLOWERING LOCUS T1 ( FT1 ), a mobile signaling protein that travels from the leaves to the shoot apical meristem to promote flowering. Here, we show that the interruption of long nights by short pulses of light ("night-break" [NB ]) accelerates wheat flowering, suggesting that the duration of the night is critical for wheat photoperiodic response. PPD1 transcription was rapidly upregulated by NB s, and the magnitude of this induction increased with the length of darkness preceding the NB . Cycloheximide abolished the NB up-regulation of PPD1, suggesting that this process is dependent on active protein synthesis during darkness. While one NB was sufficient to induce PPD1, more than 15 NB s were required to induce high levels of FT1 expression and a strong acceleration of flowering. Multiple NB s did not affect the expression of core circadian clock genes. The acceleration of flowering by NB disappeared in ppd1- null mutants, demonstrating that this response is mediated by PPD1 . The acceleration of flowering was strongest when NB s were applied in the middle of the night, suggesting that in addition to PPD1, other circadian-controlled factors are required for the up-regulation of FT1 expression and the acceleration of flowering.